SURFACE INTERACTIONS AND MECHANISMS STUDY ON THE REMOVAL OF IODIDE FROM WATER BY USE OF NATURAL ZEOLITE-BASED SILVER NANOCOMPOSITES - Inglezakis, Vassilis J.; Satayeva, Aliya R.; Yagofarova, Almira; Tauanov, Zhandos; Meiramkulova, Kulyash; Farrando-Pérez, Judit; Bear, Joseph C. (MDPI AG, 2020)
In this work a natural zeolite was modified with silver following two different methods to derive Ag2O and Ag0 nanocomposites. The materials were fully characterized and the results showed that both materials were decorated with nanoparticles of size of 5–25 nm. The natural and modified zeolites were used for the removal of iodide from aqueous solutions of initial concentration of 30–1400 ppm. Natural zeolite showed no affinity for iodide while silver forms were very efficient reaching a capacity of up to 132 mg/g. Post-adsorption characterizations showed that AgI was formed on the surface of the modified zeolites and the amount of iodide removed was higher than expected based on the silver content. A combination of experimental data and characterizations indicate that the excess iodide is most probably related to negatively charged AgI colloids and Ag-I complexes forming in the solution as well as on the surface of the modified zeolites.
Keywords: natural zeolite; nanocomposites; silver nanoparticles; silver oxide; iodide removal; Type of access: Open Access